Doing Leadership Differently as Resistance: Care-Fully Reworking Aotearoa New Zealand’s Research System - Cox, B; Locke, K; Sharp, E; Rayne, A; Walker, L; Steeves, T (Wiley, 2023)
The ‘research system’ in Aotearoa New Zealand is rife with obstacles for entry and retention of diversity. The research system's complexity and longevity gives the impression of stability and fixity, but we argue it is characterised by a lack of imagination around leadership that generates change. In this article, we examine the embodied experiences of research leadership, as encountered by participants at Aotearoa New Zealand's universities and a nationally funded Centre of Research Excellence. It is within such institutions and organisations, built on colonial and patriarchal values, that experiences of marginalisation, oppression and harassment have been documented. We destabilise the apparently static nature of this ‘research system monolith’ by taking up MacLeavy, Fannin and Larner's (2021) provocation of a feminist approach to boldly do leadership differently. Drawing from interviews with researchers, we argue that resistance to, and reworking of, the research system can be found in feminist modes of practice: in the everyday, mundane practices of care-full research leadership that do leadership differently.
Keywords: 4406 Human Geography; 44 Human Society; 0406 Physical Geography and Environmental Geoscience; 1302 Curriculum and Pedagogy; 1604 Human Geography; Geography; 3709 Physical geography and environmental geoscience; 4406 Human geography